A preliminary case study: Challenges, approaches, and pressures in the policy implementation of iCGPA - Arthur, Christine Shobana (Journal of Praxis in Higher Education, 2025)
This study explores the institutional-level implementation of the integrated cumulative grade point average (iCGPA) initiative at University A, focusing on its intentions, challenges, and responses during the early stages. Introduced by the Malaysian Ministry of Higher Education to produce holistic and balanced graduates, iCGPA seeks to complement a decade-long effort under outcome-based education (OBE). However, achieving these objectives remains elusive. Using a qualitative approach, interviews with Academic Standards Quality staff and Heads of Departments revealed key issues, including the absence of collaboration between researchers and policymakers, and the reliance on a top-down policy approach. The study highlights the role of isomorphic pressures—coercive, mimetic, and normative—in shaping policy adoption and highlights the need for evidence-based policymaking to balance standardisation with adaptability. These findings provide valuable insights for policymakers and higher education institutions to refine strategies for future policy implementation.